Contributions of Cognitive Neuroscience for the training of science teachers: a review of academic works from Brazilian postgraduate programs between the years 2012-2022 (Research, Society and Development, 2022)
In view of the ever present changes in education, new public policies and methodologies have pointed to the need to redefine teacher training curricula and, consequently, pedagogical practices. It is in this sense that the discussion on neuroscience relates to the learning process, as it provides educators with teaching and learning modes capable of offering stimuli that favor the reorganization of the student's developing nervous system, resulting in greater behavioral changes. Aligned with this aim, and seeking to contribute to the continuing education of science teachers, this research investigates how the theme of neuroscience allied to the training of science teachers has been studied in Brazil by conducting a survey in the Brazilian Digital Library of Theses and Dissertations and an analysis of the works produced by postgraduate programs between 2012 and 2022. This is a qualitative-quantitative study, which implies the analytical discussion of quantitative data, and is characterized as "state-of-the-art", since it focuses on mapping and analyzing a given body of knowledge in a given period. We concluded that there is a scarcity of studies on how cognitive neuroscience may contribute to the education of science teachers, revealing the need for further research to expand this debate and its application to the work of these educators.